Sugar Accumulation in Sugarcane: Carrier-mediated Active Transport of Glucose - Gayler, K. R. (1972)
The rate-limiting reaction for glucose uptake in storage tissue of sugarcane, Saccharum officinarum L., appears to be the movement of glucose across the boundary between the free space and the metabolic compartments. The mechanism for uptake of glucose across this boundary has been studied using 3-O-methyl glucose, an analogue of glucose which is not metabolized by sugar-cane tissue. This analogue is taken up by sugarcane storage tissue at a similar rate to glucose. Its rate of uptake follows Michaelis-Menten kinetics, Km = 1.9 mm, and it is competitively inhibited by glucose, Ki = 2 to 3 mm. Glucose uptake is similarly inhibited by 3-O-methyl glucose. Uptake of 3-O-methyl glucose is energy-dependent and does not appear to be the result of counterflow of glucose. It is concluded that glucose and 3-O-methyl glucose uptake across the boundary between the free space and the metabolic compartment in this tissue is mediated by an energy-dependent carrier system capable of accumulating the sugars against a concentration gradient.